Metadata Description Framework for Integration of Bioinformatics Information Resources: A Case of iBIRA - Ram, Shri; Laxman Rao, N. (DESIDOC Journal of Library & Information Technology, 2014)
Bioinformatics emerged as a new discipline dedicated to the answer the queries about life science using computational approaches. The basic aim of bioinformatics is to create databases, analyse data sets and managing data generated through large-scale projects such as Human Genome project (HGP). It covers a wide variety of traditional computer science domains, such as data modeling, data retrieval, data mining, data integration, data managing, data warehousing, and simulation of biological information generated through laboratory and field experiments. Due to varied form, nature, and activities in the field of bioinformatics, presenting the information in cohesive fashion is major challenge. The bioinformatics information resources are heterogeneous in nature. Integration and interoperability of information is one of the biggest challenges in this field. Bioinformatics, as an emerging field, needs attention towards metadata application for resource discovery. This paper discusses the metadata element set description framework for integration of various information resources related to the field of bioinformatics available over internet. A web-based tool iBIRA: Integrated Bioinformatics Information Resources Access has been designed and developed for integration of bioinformatics information resources. Dublin Core metadata element set has been used for description of information resources and XML schema has been used for interoperability of information resources with others. A database has been designed using structure query language (SQL)–database management system and hypertext preprocessor (PHP)–as web programming languages for integration of bioinformatics resources. The database is designated to categorise various resources into biological database, institutions, journals, patents, software tools, web-servers, etc., and the search result is presented in the form of ‘tree view’. Each of these categories of the resources has been analysed for their metadata element set as per the DCMI terms. http://dx.doi.org/10.14429/djlit.34.6254